K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

25 tháng 1 2017

Ta có: \(A=1+2+2^2+...+2^{59}\)

\(\Rightarrow2A=2+2^2+2^3+...+2^{60}\)

\(\Rightarrow2A-A=2^{60}-1\)

\(\Rightarrow A=2^{60}-1\)

\(B=4^{25}.1024=2^{30}.2^{10}=2^{40}\)

\(2^{60}-1>2^{40}\) nên A > B

Vậy A > B

25 tháng 1 2017

sao còn lại là A=2^60-1 v bn

15 tháng 11 2015

a=5^120

b= 8^60

 vì 5^120= 25^60 >8^60

=> a>b

12 tháng 7 2016

Bài 1: a) (2x+1)​2 =​ 25

               (2x+1)​2 = 5​2

=> 2x + 1 = 5           hoặc      2x+1 = -5

=> x=2                   hoặc       x=-3

  b) 2x+2 - 2​x = 96

<=> 2​x . 2​2 - 2​x = 96

<=> 2​x(4-1) =96

<=>2​x = 96 :3 = 32 = 2​5 

<=> x = 5

c) (x-1)​3 = 125

<=> (x-1)​3 = 5​3

<=> x-1=5

<=>x= 5 +1 = 6

 
12 tháng 7 2016

Bài 2 :

a) Ta có :  7​6+7​5-7​4 
              =7​4(7​2+7-1) 
              =7​4.55=7​4.5.11 chia hết cho 11 

b) Ta có:

81​7-27​9-913
=(3​4)​7- (3​3)​9-​   (3​2)​13 
=328 - 327- 3​26
=326 (3​2-3-1) 
 = 326.5 = 31​3.3​2.5 = 45.31​3 chia hết cho 45

10 tháng 8 2020

\(A=\left(\frac{1}{2^2}-1\right)\left(\frac{1}{3^2}-1\right)\left(\frac{1}{4^2}-1\right)....\left(\frac{1}{2013^2}-1\right)\left(\frac{1}{2014^2}-1\right)\)

\(\Leftrightarrow A=\left(\frac{1}{4}-1\right)\left(\frac{1}{9}-1\right)\left(\frac{1}{16}-1\right)....\left(\frac{1}{4052169}-1\right)\left(\frac{1}{\text{​​}\text{​​}4056196}-1\right)\)

\(\Leftrightarrow A=\frac{-3}{4}.\frac{-8}{9}.\frac{-15}{16}.....\frac{-4056195}{\text{​​​​}4056196}\)

\(\Leftrightarrow A=\frac{\left(-1\right)3}{2^2}.\frac{\left(-2\right)4}{3^3}.\frac{\left(-3\right)5}{4^2}.....\frac{\left(-2013\right)2015}{\text{​​​​}2014^2}\)

\(\Leftrightarrow A=\frac{\left(-1\right)\left(-2\right)....\left(-2013\right)}{2.3...1014}.\frac{3.4......2015}{2.3......2014}\)

\(\Leftrightarrow A=\frac{-1}{1014}.\frac{2015}{2}=\frac{-2015}{4028}\)

VÌ \(\frac{-2015}{4028}< \frac{-1}{2}\)

\(\Rightarrow A< \frac{-1}{2}\Leftrightarrow A< B\)

10 tháng 8 2020

Ta có \(A=\left(\frac{1}{2^2}-1\right)\left(\frac{1}{3^2}-1\right)...\left(\frac{1}{2014^2}-1\right)=\frac{-3}{2^2}.\frac{-8}{3^2}...\frac{-4056195}{2014^2}\)

\(=-\left(\frac{1.3}{2^2}.\frac{2.4}{3^2}...\frac{2013.2015}{2014^2}\right)=-\left(\frac{1.3.2.4...2013.2015}{2.2.3.3...2014.2014}\right)\)

\(=-\left(\frac{\left(1.2.3...2013\right)\left(3.4.5...2015\right)}{\left(2.3.4...2014\right)\left(2.3.4...2014\right)}\right)=-\frac{2015}{2014.2}=-\frac{2015}{4028}< \frac{-2014}{4028}< \frac{1}{2}=B\)

=> A < B